Development of KONEL e-module with website-based exe-learning media on electron configuration material - Aisyah, Ratna Sari Siti (Edukimia, 2023)
Abstract High school students have many difficulties in understanding electron configuration material because most of the material is abstract and the method used is only in the form of lectures and power point media. This development research aims to produce learning media products in the form of KONEL E-Modules with website-based Exe-Learning media  on electron configuration materials. This research is designed with a 4D model with stages of defining (Define), designing (Design), Development (Develop), and Disseminnate (Disseminnate). This KONEL E-Module was validated by 6 experts with the average value of material validation results was 0.87 and the media was 0.89, both of which were declared valid. Then the KONEL E-Module was implemented with a limited test to 31 students of grade X-7 SMAN 1 Jawilan to determine students' responses to the developed media by obtaining a percentage of 86.23% which was included in the very good category.Keywords: KONEL E-Module, website-based Exe-Learning media, Electron configuration, 4D